2000
DOI: 10.1046/j.1471-4159.2000.0750788.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidative Stress on Phospholipid Signaling in Rat Cultured Astrocytes and Brain Slices

Abstract: Although reactive oxygen species (ROS) are conventionally viewed as toxic by-products of cellular metabolism, a growing body of evidence suggests that they may act as signaling molecules. We have studied the effects of hydrogen peroxide (H 2 O 2 )-induced oxidative stress on phospholipid signaling in cultured rat cortical astrocytes. H 2 O 2 stimulated the formation of phosphatidic acid and the accumulation of phosphatidylbutanol, a product of the phospholipase D (PLD)-catalyzed transphosphatidylation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
(40 reference statements)
5
36
0
Order By: Relevance
“…4B) and the level of InsP 3 by 14.3% (control set at 100% of InsP 3 level; P,0.05; Fig. 4C) confirming the fact that ROS can activate PLC (Servitja et al, 2000;Vaarmann et al, 2010;Wang et al, 2001). The PLC activity and InsP 3 level in the brain supernatant samples cotreated with H 2 O 2 and vitamin E or Trolox were similar to the control samples (around 100%), indicating that vitamin E and Trolox, by preventing lipid peroxidation, prevent PLC activation and generation of InsP 3 (Fig.…”
Section: Stimulation Of Astrocytes With Atp Increases the Rate Of Rossupporting
confidence: 57%
See 1 more Smart Citation
“…4B) and the level of InsP 3 by 14.3% (control set at 100% of InsP 3 level; P,0.05; Fig. 4C) confirming the fact that ROS can activate PLC (Servitja et al, 2000;Vaarmann et al, 2010;Wang et al, 2001). The PLC activity and InsP 3 level in the brain supernatant samples cotreated with H 2 O 2 and vitamin E or Trolox were similar to the control samples (around 100%), indicating that vitamin E and Trolox, by preventing lipid peroxidation, prevent PLC activation and generation of InsP 3 (Fig.…”
Section: Stimulation Of Astrocytes With Atp Increases the Rate Of Rossupporting
confidence: 57%
“…ROS can activate such release of Ca 2+ from endoplasmic reticulum (ER) stores; a mechanism which has been thought to be mediated by ROS-mediated activation of RyR receptors on the ER (Camello-Almaraz et al, 2006). However, there is also strong evidence that ROS activates PLC, which ultimately contributes to Ca 2+ release (Servitja et al, 2000;Vaarmann et al, 2010). These indirect, PLC-mediated, ROSinduced Ca 2+ signals are likely to play an important role in the brain, where there are high levels of oxidisable polyunsaturated fatty acids and high ROS load due to high oxygen consumption (Halliwell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, H 2 O 2 can modify the activity of Ca 2ϩ pumps involved in Ca 2ϩ homeostasis, such as the sarcoendoplasmic reticulum Ca 2ϩ -ATPase (SERCA) (17) and plasma membrane Ca 2ϩ -ATPase (17). Furthermore, enzymes involved in Ca 2ϩ signaling pathways, such as phospholipase C (PLC) ␥1 (18) and phospholipase D (19) are also targets. However, most of the previous studies employed high concentrations of H 2 O 2 , and it is questionable whether such diverse actions of H 2 O 2 on * This work was supported in part by Korea Health 21 R & D Project, the Ministry of Health & Welfare, and Republic of Korea Grants 03-PJ1-PG3-21400-0005, 02-PJ1-PG3-20706-0001, and A050002.…”
mentioning
confidence: 99%
“…intracellular space was not important since preincubation of a calcium ionophore, A23187, as well as several calcium channel inhibitors such as flunarizine and neomycin did not alter the UVC-stimulated PLD activity in Vero 76 cells (data not shown). Similarly, PLD activity stimulated by hydroperoxide Servitja et al, 2000) or pervanadate (Oh et al, 2000) has been reported to be dependent on extracellular calcium. On the other hand, other stimulants of PLD activity, such as phorbol ester (Huang et al, 1992), α-thrombin (Garcia et al, 1992), or oleate , are not dependent on extracellular calcium.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, p38 MAPK (mitogen-activated protein kinase) and PKC mediated the activation of PLD by pervanadate and diperoxovanadate (Natarajan et al, 1996;Min et al, 2002;Kim et al, 2003). In astrocytes and fibroblasts, H2O2-induced PLD1 stimulation was inhibited by PKC inhibitors and was almost completely suppressed by PKC downregulation (Min et al, 1998;Servitja et al, 2000). However, in other cell lines such as PC12 and the vascular smooth muscle cells, which exhibit only PLD2 activity, PLD activation was shown to be independent of PKC activity (Ito et al, 1997;Taher et al, 1998).…”
Section: Introductionmentioning
confidence: 99%